2015
DOI: 10.1016/j.tibs.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Ready, pause, go: regulation of RNA polymerase II pausing and release by cellular signaling pathways

Abstract: Promoter-proximal pausing by RNA polymerase II (Pol II) is a well-established mechanism to control the timing, rate, and possibly the magnitude of transcriptional responses. Recent studies have shown that cellular signaling pathways can regulate gene transcription and signaling outcomes by controlling Pol II pausing in a wide array of biological systems. Identification of the proteins and small molecules that affect the establishment and release of paused Pol II is shedding new light on the mechanisms and biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 108 publications
2
115
1
1
Order By: Relevance
“…Genome-wide studies have demonstrated that promoter proximal Pol II pausing is common and that increased transcription from these genes results from release of the paused Pol II and increased elongation (40,41). It is proposed that promoter paused Pol II favors a synchronized response to environmental stimuli (42).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide studies have demonstrated that promoter proximal Pol II pausing is common and that increased transcription from these genes results from release of the paused Pol II and increased elongation (40,41). It is proposed that promoter paused Pol II favors a synchronized response to environmental stimuli (42).…”
Section: Discussionmentioning
confidence: 99%
“…G4 formation may be favored by formation of an R-loop on the C strand (Fragkos et al 2015), and G4/OGRE elements could function as a structural switch: folded or unfolded. Alternatively, replication origins could be activated at pre-RCs and then transiently stall at the proximal G4 on the leading strand, a phenomenon similar to transcriptional pausing (Liu et al 2015). This mechanism could be used to start initiation on the opposite strand, similarly to the model proposed for the DBF4 replication origin (Romero and Lee 2008).…”
Section: G-rich or G4 Signatures At Replication Origins And Nucleosommentioning
confidence: 97%
“…The pausing of Pol II 20–60 bp into the transcription unit poises genes for rapid induction in response to external stimuli and maintains promoter-proximal regions in a nucleosome-depleted state [54]. The transcription elongation factor DSIF (human ortholog of the yeast Spt4–Spt5 complex) acts in concert with another protein complex, NELF, to establish promoter-proximal pausing of Pol II [55] (Figure 2). Release from pausing is triggered by phosphorylation of NELF and Spt5 by P-TEFb (CDK9-cyclin T complex), upon which NELF dissociates from the polymerase and DSIF becomes a positive elongation factor [55].…”
Section: Paf1c Regulates Gene Expression Through Diverse Mechanismsmentioning
confidence: 99%